The Impact of Short Stories for English as A Second Language and Foreign Language Students: A Literature Review - Zanyar Nathir Ghafar; Putri Amalia Zubaedah (Journal Of Social Science (JoSS), 2023)
Background: The importance of reading and comprehending short stories has been focused by many experts, particularly those who work in English as a second or foreign language (ESL) and (EFL). There has been a significant amount of investigation on how effectively employing brief narratives might aid ESL students' instruction. Aim: Many educators and researchers have been looking into more efficient approaches to assisting pupils in realizing their full academic potential as qualified readers. They support the idea that it would be beneficial to add literary works into language education, and they believe this would be beneficial. Suppose students of English as a second language (ESL) are taught literature in general and short stories in particular, effectively by ESL instructors. In that case, ESL and EFL students may get various benefits. Short tales, in particular, may be very beneficial. Method: Several databases have been utilized to search current research. Seventeen relevant papers were selected for evaluation on this topic. They were investigated extensively, and the results were conveyed normatively. Findings: This review paper summarizes the publications' most significant results and explains that short stories may be convincing to enhance vocabulary, self-motivated, and professionalism; this study's goal was to understand better how reading brief stories by students affected their comprehension processes. At the same time, they are correctly chosen and taught. The recommendation is obtained from the review, summarizing the most significant to applying ESL and EFL classes.